The rise in bilateral mastectomies: Evidence, ethics, and physician's role. (October 2016) - Yang, Y. Tony; Pike, Elizabeth R.; Rose, Christopher M.; Botnick, Leslie E.
Abstract: This viewpoint reviews double mastectomies' trend, medical evidence and ethical considerations, as well as the role of the physician in counseling the patient. It concludes that physicians should encourage patients to pursue alternative preventive measures, and promote bilateral mastectomies only for high-risk patients for whom the potential benefits of the surgery are sufficient to justify the surgery's increased risks.